RETRACTED: Reward dan punishment sebagai faktor-faktor determinan kepuasan kerja - Mardalena Mardalena; Sarinah Sarinah; Yesi Elfisa (Jurnal Konseling dan Pendidikan, 2022)
RETRACTED:Mardalena, M., & Sarinah, S. (2023). Reward dan punishment sebagai faktor-faktor determinan kepuasan kerja.Jurnal Konseling dan Pendidikan , 10(4), 628-637.The publisher has retracted this article based on the following reason:The author's disclosure to the editor for permission to republish in another journal.The author is not allowed to withdraw submitted manuscripts, because the withdrawal wastes valuable resources that editors and referees spend a great deal of time processing submitted manuscripts, money, and works invested by the publisher.The author and his/her affiliation will be blacklisted for publication in this journal in the future. Even his/her previously published articles will be removed from our online system.